How is Bariatric Surgery Improving the Quality of Life of Obese Patients: A Portuguese Cross-Sectional Study - Silva, José (2018)
Introduction: Obesity is often accompanied by psychological distress and both can reduce patients’ quality of life. Bariatric surgery is proven to be a good method to reduce weight and to alleviate comorbidities, leading ultimately to an improvement in quality of life.Material and Methods: The authors studied 80 patients enrolled in the Multidisciplinary Bariatric Unit of a central hospital in Porto, Portugal. Patients submitted to Roux-en-Y gastric bypass and sleeve procedures were compared. Laboratory parameters were collected from patients’ files. Quality of life and psychological state - depression and anxiety, were evaluated using the Portuguese versions of the Medical Outcomes Study SF-36 and the hospital anxiety and depression scale, respectively, within one to two years of the surgery.Results: A total of 51 patients were operated and completed a quality of life evaluation, while 21 patients were in a pre-operatory group (control). Patients subjected to bariatric surgery had higher scores of SF-36 and lower scores in both hospital anxiety and depression scale (anxiety and depression) subscales (p < 0.001); SF-36 presented a Pearson correlation coefficient of 0,475 (p = 0.004) with hemoglobin A1c. Sleeve had better results in the hospital anxiety and depression scale-depression subscale (p = 0.073).Discussion: In this population, bariatric surgery led to better results, regarding both metabolic and psychological evaluations. No significant differences were found between gastric bypass and sleeve. However, further analyses must be performed.Conclusion: This study supports the theory that bariatric surgery contributes to the improvement of obese patients’ quality of life and psychological state.